(3GdLGeY aj CMGOjK GdYHGOGJs - (3YdhT, YHO GdSdGe Hf eMeO Hf YeQs ((3HjQhJ (B:s (3OGQ GHf MRe ddWHGYI hGdfTQ hGdJhRjY,s, 1999)
(3jJfGhd GdcJGH GdCMGOjK GdJj JJfGhd GdYHGOGJ, eKd CMGOjK aj GdUdGI hGdWgGQI hGdML hGdUjGe hGdRcGI(B.s
(3cTGaGJ (B: (3eL(B. 3.s
Keywords: (3GdMOjKs -- (3LhGeY Gdafhfs; (3GdYHGOGJ aj GdMOjKs